2015
DOI: 10.3171/2015.1.spine13864
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for dural tear in patients undergoing lumbar spine surgery

Abstract: OBJECT The purpose of this prospective cohort study was to identify risk factors for incidental durotomies in lumbar spine surgery. The authors hypothesized that the incidence of durotomy would be higher in cases involving multiple operations. METHODS The authors prospectively evaluated 523 patients who underwent lumbar and thoracolumbar spine surgery. They compared data on patients in whom a dural tear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 13 publications
3
44
0
1
Order By: Relevance
“…The durotomy incidence in a group of patients who underwent revision surgery was 25% (29 of 116) and was not associated with the years of experience of the surgeon performing the procedure. 38 Studies entirely composed of interbody fusion procedures, such as those conducted by Mehta et al 28 and Tormenti et al, 42 reported higher durotomy rates of 14.2% and 14.3%, respectively. The highest durotomy rate, 20%, was reported in a non-cohort-matched prospective study by Rodriguez-Olaverri and colleagues in which the authors evaluated clinical and radiographic outcomes of instrumented fusion for high-grade spondylolisthesis.…”
Section: Open Lumbar Proceduresmentioning
confidence: 99%
“…The durotomy incidence in a group of patients who underwent revision surgery was 25% (29 of 116) and was not associated with the years of experience of the surgeon performing the procedure. 38 Studies entirely composed of interbody fusion procedures, such as those conducted by Mehta et al 28 and Tormenti et al, 42 reported higher durotomy rates of 14.2% and 14.3%, respectively. The highest durotomy rate, 20%, was reported in a non-cohort-matched prospective study by Rodriguez-Olaverri and colleagues in which the authors evaluated clinical and radiographic outcomes of instrumented fusion for high-grade spondylolisthesis.…”
Section: Open Lumbar Proceduresmentioning
confidence: 99%
“…Surgical invasiveness and manipulation of dura has been reported as a general predictor of dural injury and appears to be associated with overall dural injury rates. Dural injury incidence in a group of patients who underwent revision surgery was 25% and was not associated with the years of experience of the surgeon (16) . In our study, the ratio of dural injury in revision cases was found to be 25.86% (15/58).…”
Section: Discussionmentioning
confidence: 87%
“…Fortunately in the last decades, the prevalence of dural tears was decreased due to the increasing experience of spine surgeons, when performing minimal invasive techniques such as FED. All authors conclude that the key point is the prevention and the immediate recognition and treatment, in order to avoid the long-term sequelae of dural tears [40]. Fig.…”
Section: Discussionmentioning
confidence: 95%